DFT based Investigation of Structural, Thermodynamic, Mechanical and Electronic Properties of RuVZ (Z: As, Bi, Sb) Half-Heusler Semiconductors - Oyindenyifa Nelson, Nenuwe; Oghogho, Omagbemı (VNU Journal of Science: Mathematics - Physics; Vol 38 No 3DO - 10.25073/2588-1124/vnumap.4705, 2022)
Half-Heusler (hH) alloys are an intriguing class of materials with significant potential for applications in spintronics, thermoelectrics, optoelectronics, and magnetoelectronics due to their unique adjustable properties. In this work, we have investigated the structural, thermodynamic, mechanical, and electronic properties of RuVZ (Z: As, Bi, Sb) half-Heusler materials using the density functional theory (DFT) as implemented in the quantum espresso computational suite. The structural, thermodynamic, and mechanical properties were also predicted using the linear response density functional perturbation theory. We observed that the hH alloys are non-magnetic semiconductors and have an indirect narrow band gap. The band gap values and lattice constants for RuVSb and RuVAs cubic crystals are consistent with published reports. RuVBi has a lattice constant of 6.18  and a band gap of 0.16 eV.  The elastic parameter results obtained satisfy Born's stability requirements, suggesting mechanical stability of the hH materials. All three alloys are found to be ductile. The RuVZ alloys obey the Dulong-Petit law at heat capacity of 74.7, 74.5, and 74.3 J mol -1 K -1 and temperatures of 556, 754, and 775 K, respectively. The Debye temperature of 353.75K suggests that the RuVAs alloy is the hardest, with a significant Debye sound velocity (2997.12 m/s) and will have high thermal conductivity.